Photoelectron spectroscopy investigations of recombination contacts for tandem organic solar cells - Olthof, S; Timmreck, R; Riede, M; Leo, K (American Institute of Physics, 2012)
Recombination contacts play an important role in highly efficient organic tandem solar cells. We present a photoelectron spectroscopy study on contact systems that have previously been shown to work efficiently as recombination contacts. Here, the conversion of an electron current into a hole current is realized either by insertion of gold clusters or by a highly doped pn-junction. From the measured energy level alignments, we show that the working principles of these two approaches are significantly different. For gold clusters, the recombination current is promoted by an accumulation of charge carriers, while for doped pn-junctions, it is achieved by tunneling through a depletion layer. © 2012 American Institute of Physics.